Ruolo della chirurgia bariatrica nel paziente con malattia renale cronica - Rosa Grimaldi; Maria Luisa Muci; Silverio Rotondi; Lida Tartaglione; Mario Rizzello; Francesca Abbatini; Gianfranco Silecchia; Sandro Mazzaferro (AboutScience Srl, 2016)
Abstract non disponibile